The red planet, a survey of Mars - Kiefer, Walter S.; Clifford, Stephen Mark, 1952-; Treiman, Allan H.; orcid:0000-0002-8073-2839; orcid:0000-0001-6741-5460; orcid:0000-0003-0771-1713 (Lunar and Planetary Institute, 1997)
LPI slide set converted to a PowerPoint set by the staff of the Spacecraft Planetary Imaging Facility, Cornell University An overview of Mars, including its volcanoes, the Valles Marineris canyon system, features formed by running water, the SNC meteorites, and its two small moons, Phobos and Deimos. This is the second edition, revised in 1997 to include recent images from Mars Pathfinder and the Hubble Space Telescope. compiled by Walter S. Kiefer, Allan H. Treiman and Stephen M. Clifford Earth-Mars Comparison -- Earth Telescope View of Mars (0° N, 43° W) -- Space Telescope View of Mars (0° N, 270° W) -- Viking Orbiter Mosaic (5° S, 80° W) -- Size of Valles Marineris -- Valles Marineris (12° S, 64° W) -- Landslide in Valles Marineris (10° S, 45° W) -- Tharsis Graben (38° N, 105° W) -- Hesperia Planum Ridges (29° S, 241° W) -- Size of Tharsis Volcanos -- Olympus Mons (20° N, 135° W) -- Uranius Tholus (26° N, 98° W) -- Lava Flows (33° N, 213° W) -- Mantle Convection -- Argyre Basin (50° S, 40° W) -- Sizes of Impact Basins -- Cratered Terrain (22° S, 214° W) -- Clouds Around Olympus Mons (20° N, 135° W) -- Fog in Noctis Labyrinthis (10° S, 95° W) -- Seasonal Evolution of the North Polar Cap (90° N) -- High-Resolution View of North Polar Layered Deposits (84° N, 237° W) -- South Polar Residual Ice Cap (90° S) -- The Source Region of the Outflow Channel Ravi Vallis (1° S, 42° W) -- Outflow Channels Emptying into Northern Plains of Chryse Planitia -- Streamlined Islands (20° N, 31° W) -- Valley Network (42° S, 92° W) -- Rampart Crater with Fluidized Ejecta (22° N, 34° W) -- Ocean Borealis (60° N, 40° W) -- Dust Storm at Viking 1 Landing Site (22° N, 48° W) -- Frost at the Viking 2 Lander (48° N, 226° W) -- Mars Pathfinder: Sojourner and Yogi (19° N, 34° W) -- Mars Pathfinder: Twin Peaks (19° N, 34° W) -- Impact Origin of Meteorites from Mars -- Unusual Crater: Possible Source of Martian Meteorites (24° N, 99° W) -- A Martian Meteorite -- Microscopic View of a Martian Meteorite -- Microscopic View of a Martian ...